2012
DOI: 10.5433/1679-0375.2012v33n2p117
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do emprego da radiação ultravioleta na desinfecção de esgoto sanitário

Abstract: A presente pesquisa teve como objetivo avaliar a potencialidade do uso da radiação ultravioleta (UV) como agente desinfetante de esgoto sanitário proveniente do tratamento biológico contendo concentrações de sólidos suspensos totais que variaram de 30 a 75 mg/L. Os ensaios de desinfecção foram realizados em um reator em escala de bancada de laboratório e a efetividade do processo foi avaliada empregando os microrganismos indicadores Coliformes Totais (CT) e Escherichia coli. Embora a baixa qualidade do efluent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 0 publications
1
4
0
7
Order By: Relevance
“…On the other hand, in the same test, UV radiation was not very efficient to remove total coliforms (maximum inactivation log 1,76). The biggest difficulty to the inactivation of total coliforms is also observed in several other studies in the area specific literature, including Souza et al [15].…”
Section: Tests Of Wastewater Disinfectionsupporting
confidence: 55%
See 1 more Smart Citation
“…On the other hand, in the same test, UV radiation was not very efficient to remove total coliforms (maximum inactivation log 1,76). The biggest difficulty to the inactivation of total coliforms is also observed in several other studies in the area specific literature, including Souza et al [15].…”
Section: Tests Of Wastewater Disinfectionsupporting
confidence: 55%
“…Radiation intensity measurements were carried out with a radiometer (Vilber Lourmat) with UV radiation detector sensor at the 254 nm wavelength. To determine the UV radiation dose, the route described by Daniel [14], as well as the study carried out by Souza et al [15], was followed.…”
Section: Experimental Conditionsmentioning
confidence: 99%
“…Bilotta and Daniel (2012) tested the effect of effective UV doses (123.0 and 247.0 mWscm -2 ) on effluent from secondary treatment with exposure times of 60/120 seconds and noted the inactivation of 1.6 to 5.2 log-cycles of E. coli. Souza et al (2012) in one of their UV assays observed that 317.1 mWscm -2 were required to inactivate 3.7 and 2.0 log-cycles of E. coli and CT, respectively. However, a dose of 42.28 mWscm -2 was able to disinfect approximately 5 log of the same microorganisms.…”
Section: Resultsmentioning
confidence: 99%
“…As doses de radiação foram calculadas pelo produto da intensidade de radiação pelo tempo de exposição, de acordo com Souza et al (2012).…”
Section: Figura 1 -Fluxograma Dos Experimentos Realizadosunclassified